LIMITATION OF HUMAN RIGHTS WITHIN THE CONTEXT OF GLOBAL CRISES – A PROBABLE POSSIBILITY (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Limitation of Human Rights within the Context of Global Crises – A Probable Possibility.Human rights treaties and laws are designed to protect the inherent and universal rights of all people by affirming human value, dignity and the primacy of life. Religious freedom is one of the paramount universal human rights which needs to be asserted and protected. The world we live in can be defined as being in a continue state of crisis, or permacrisis. Various scholars warn that, in times of crisis, liberties and rights may be limited, and even suspended, and this would be done in order to preserve and facilitate local and global security. There are current developments whereby governments are considering the withdrawal from UN treaties in order to address political, economical and security concerns. Technology and digitalisation contribute to increased awareness about human rights while also compounding the exacerbation and deepening of the varying human crises we encounter today. Therefore, the responsibility to educate and inform society with respect to human rights and their importance needs to be shared across all spheres of public influence.